Topology of a Computer-Supported System for Remote Monitoring and Management of Flotation in the Copper Mine "Veliki Krivelj", Bor, Yugoslavia - Slobodan B. Vujic (International Mineral Processing Congress, 2003)
"Some twenty years ago, during construction of flotation in the “Veliki Krivelj” copper and non-metallic mine Bor, a computer supported system for remote controle of technological process was installed. Nowadays, the major part of equipment of this system is worn-out and technically old-fashioned. Having this in mind a decision was made to design a new computer supported information-management system for Flotation. The paper presents a concept and features of project solutions.For the requirements of remote monitoring and management of technological process in Flotation of “Veliki Krivelj”, Copper and non-metallic minerals mine in Bor, Yugoslavia (hereinafter: CNM Bor), a measuring-regulation equipment was implemented and a computer control system, adjusted for that time, built some twenty years ago. The major part of this equipment is today worn out and technically out of date.Having estimated that production and business activities could hardly be more efficient, operative and successful on one hand, and available mineral and other resources rationally exploited, the CNM Bor made a decision in 1999 to improve information-management function of Flotation. The idea was that the set task be realized through development and introduction into practice up-to-date integrated and computer-supported production-business information-management system. The first logic step in completion of this task refers to engineering-creative determination of information management system (hereinafter: IMS), namely to project elaboration.When considering the real system from technical, technological, organization, monitoring-management, logistic and business aspects, the Project on IMS of Flotation, should provide a rational, modern and, for the real system conditions, complete solution. The Project solutions should be based on the most recent knowledge from computer and measuring-regulation technics as well as from CIM concept (Computer Integrated Manufacturing)."